A Microscopic Look Into The Occupational Stress And Quality Of Life: Insightful Study Between Blue- And White-Collar Shoe Employees Of Agra (Journal of Namibian Studies : History Politics Culture, 2023)
Employee stress in the workplace is becoming more widely acknowledged around the world as the demands of modern work life become more complicated, but there is a lack of research in the existing literature that evaluates occupational stress and quality of life among blue-collar and white-collar shoe workers in Agra.  The present study examines the occupational stress among the blue-collar and white-collar shoe workers of Agra. The study was conducted among 72 white-collar and 137 blue-collar workers by using standard tools: Occupational stress Inventory and Total Quality of Life questionnaire to assess the level of Occupational stress and quality of life among the selected samples. The findings of the study reported that white-collar employees reported high workloads, work under tight deadlines, feel unsupported by needed resources, have poor social support, poor sense of role expectations, and reported conflicting demands from supervisors but experiencing less exposure to unhealthy environments as compared to their counter blue-collar shoe employees. Moreover, the result indicates that an employee’s age and length of employment strengthen their ability to cope and increase their level of independence. Similarly, educated workers reported better physical health, self-care concerns, and less exposure to unhealthy environments, but in contrast also experienced high levels of occupational stress, task overload, and role ambiguity. Furthermore, income is negatively associated with work and interpersonal stress whereas long working hours are positively associated with workers’ interpersonal, social-occupational stress and exposure the harmful physical environments.